INNOVATIVE PEDAGOGICAL TRENDS OF THE DUAL EDUCATION SYSTEM IN HIGHER EDUCATIONAL INSTITUTIONS - Narbayeva , Malokhat (Educational Research in Universal Sciences, 2023)
This article explores innovative pedagogical trends within the dual education system of Higher Educational Institutions (HEIs). It delves into various aspects, including blended learning, project-based learning, industry-integrated curricula, technology integration, collaboration between HEIs and industry, and student-centered approaches. The discussion aims to uncover the significance of these trends in bridging the gap between theoretical knowledge and practical skills, preparing students for the workforce.